2016
DOI: 10.1297/cpe.25.59
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma complicated by cyanotic congenital heart disease: a case report

Abstract: Abstract.Coincidental cyanotic congenital heart disease and pheochromocytoma is uncommon, although some cases have been reported. We describe a girl aged 15 yr and 11 mo with pheochromocytoma and tricuspid atresia treated by performing the Fontan surgery. The patient did not have any specific symptoms of syndrome related to pheochromoytoma or a family history of pheochromocytoma. During cardiac catheterization, her blood pressure increased markedly, and an α-blocker was administered. Catecholamine hypersecreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…We performed genetic testing in only two patients, but there was no genetic mutation related with PHEO/PGL. To date, four patients from two studies have been reported to had performed genetic testing including SDHx , TMEM127 , and MAX , and only one patient had pathogenic missense SDHB mutation . .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed genetic testing in only two patients, but there was no genetic mutation related with PHEO/PGL. To date, four patients from two studies have been reported to had performed genetic testing including SDHx , TMEM127 , and MAX , and only one patient had pathogenic missense SDHB mutation . .…”
Section: Discussionmentioning
confidence: 99%
“…PHEO or PGL is a catecholamine‐producing tumor that arises from sympathetic lineage–derived cells of the adrenal medulla or the extra‐adrenal paraganglia . Cyanotic congenital heart disease (CHD) was speculated to be associated with PHEO/PGL because of case reports of PHEO/PGL that developed in relatively young patients with cyanotic CHD . Opotowsky et al recently reported that patients with cyanotic CHD had increased odds ratio (6.0; confidence interval, 2.6–13.7; P < 0.0001) for PHEO/PGL development compared with those without cyanotic CHD in a multicenter case series …”
Section: Introductionmentioning
confidence: 99%
“…350,351 Neuroendocrine tumors such as pheochromocytoma and paraganglioma have been documented in the setting of cyanotic CHD going back to the 1960s. [352][353][354][355] Chronic hypoxia was hypothesized to be the trigger on the basis of observations of a higher incidence in high-altitude dwellers. 356 A number of genes have been identified that are associated with these neoplasms, including mitochondrial succinate dehydrogenase (SDH) complex subunits A, SDHB, SDHC, SDHD, and SDH5 and Von Hippel Lindau tumor suppressor genes.…”
Section: Special Populationsmentioning
confidence: 99%
“…Previous studies have reported the hypersecretion of CAs in a hemodialysis patient with pheochromocytoma 19 and another patient with pheochromocytoma. 20 Thus, it will be worthwhile to try to detect CAs in clinical plasma samples in the future. Limited numbers of blood samples were included in this study, and in the future, more samples as well as clinical samples should be obtained for further analysis.…”
Section: The Analysis Of a Real Plasma Samplementioning
confidence: 99%